5x-(4-2x)=7

Simple and best practice solution for 5x-(4-2x)=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-(4-2x)=7 equation:


Simplifying
5x + -1(4 + -2x) = 7
5x + (4 * -1 + -2x * -1) = 7
5x + (-4 + 2x) = 7

Reorder the terms:
-4 + 5x + 2x = 7

Combine like terms: 5x + 2x = 7x
-4 + 7x = 7

Solving
-4 + 7x = 7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 7x = 7 + 4

Combine like terms: -4 + 4 = 0
0 + 7x = 7 + 4
7x = 7 + 4

Combine like terms: 7 + 4 = 11
7x = 11

Divide each side by '7'.
x = 1.571428571

Simplifying
x = 1.571428571

See similar equations:

| x^2+19=119 | | 10x=x-3 | | x/(lnx)=4 | | (-1/2)^5 | | 14+3z-8-5z= | | x^2-25=144 | | 11y-14=7+14y | | 16x^2-25x=-9 | | 6x-6=3(x-2) | | 5w+10=2(4w+10) | | 1h+h=9 | | Y+3-28= | | w^2+12w-20=0 | | 3(x+2)=7(2x-1) | | 3w+10=3w+10 | | f(x)=3x^2+7x-5 | | 5y-19=12 | | 10x+9y=1200 | | 9p+7=6p+5 | | f(3)=3x^2-4x+5 | | 3ln(x+3)=-6 | | 2n-12=3n+9 | | (x+69)+2x=180 | | 10=5m(m-5) | | 8w+12=180 | | x^2-(-5)x+c=0 | | -122=2x-7(-3x-22) | | -15.00+0.39x=14.95+0.13 | | f(-2)=3x^2-4x+5 | | x^2-2x+y^2-6y-27=0 | | 9-5y=14 | | 9-5y=12 |

Equations solver categories